Fenomena Tajdīdu An-Nikah Di Kelurahan Ujung Kecamatan Semampir Kodya Surabaya - Mohammad Nafik (LP2M Institut Agama Islam Negeri (IAIN) Kediri, 2016)
Tajdīdu an-Nikah is principle a process of marriage agreement between a man and a girl which have been legally married. It is conducted because of some reasons. Even though, there is no basis of law both syar’i and positive law, Tajdīdu an-Nikah practice can be found in entire place of Indonesian country. Tajdīdu an-Nikah becomes one of solutions to repair marriage agreement and not to repeat marriage agreement. Tajdīdu an-Nikah which is conducted by the couple is as an alternative way to add the betterment between them, and to expect barokah in their family in order to live welfare and serenely because it contains tajammul (beauty) and ihtiyati (care). This article is based on a research conducted in Ujung village, Semampir, Surabaya Utara by using qualitative approach. The findings show that Tajdīdu an-Nikah phenomena is cause by some factors namely religious belief and tradition developed in the community. Tajdīdu an-Nikah is believed that it can give a problem solution on un-having children, unsmoothing economy, using wali hakim in the first marriage agreement, or wandering in a long time one of the couple. Some of them are based on worry (careful), or afraid if the relation of the couple has been not halal.